Perlindungan Hukum terhadap Traditional Knowladge di Indonesia dalam Sistem Hak Kekayaan Intelektual Berdasarkan World Intelectual Property Organitation - Sofari, Muhammad Fardi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
When it comes to traditional knowledge, such as art, culture, and other types of local wisdom, Indonesia has a lot of potential as an archipelagic nation with many different tribes that each have their own unique traditions, arts, and culture. Its exceptional potential is a national or state asset that has to be safeguarded so that it may continue to grow and ultimately benefit society. In reality, most of the traditional wealth formerly held by residents of the archipelago has either vanished or been moved to other nations. Protecting traditional knowledge via intellectual property rights such as copyrights, patents, plant varieties, industrial designs, and trademarks is an idea that the World Intellectual Property Organization (WIPO) has given considerable thought to. It may be challenging to secure traditional knowledge via intellectual property rights in practice because to problems with ownership, novelty, duration, fixation, invention, and novelty.